Sinergitas Pemerintah Daerah dan Dewan Perwakilan Rakyat Daerah Dalam Pengawasan Otonomi Khusus di Kabupaten Sorong - Alam, Siti Nur Annisa; Sattu, Sattu; Ichwan, Saiful; Andi Hasan, Jondeway (Jurnal Fase Kemajuan Sosial dan Politik: Faksi, 2023)
This research aims to find out how, obstacles and solutions to the synergy of the Regional Government and the Regional People's Representative Council in Supervising Special Autonomy in Sorong Regency. The research approach used uses Qualitative Research. The selected informants consisted of the Head of the BPKAD Budgeting Division; Head of Sub. BPKAD Treasury Technical Development and Guidance Sector; Head of BPKAD Verification Division; Head of the Legal and Trial Section of the DPRD Secretariat. Data collection techniques include interviews, observation and documentation. The results of the research show that: (1) BPKAD and Sorong Regency DPRD in carrying out supervision related to Special Autonomy are considered to be still not optimal, this is judged from the relationship between these two agencies which has not been established well enough. (2) Obstacles that arise in the supervision of Special Autonomy by BPKAD and DPRD include, among others, the community is not really involved in monitoring Special Autonomy, the Papuan People's Assembly (MRP) does not play an active role, there is a lack of communication between DPRD and Regency Government, and the DPR faction has not yet been formed. Special Autonomy at the district/city level. (3) The solutions offered by the resource persons as an offer to the obstacles experienced include: strengthening relations between BPKAD and DPRD as the control holder over the supervision of Special Autonomy in Sorong Regency, the community is involved in the supervision of Special Autonomy, the MRP is guided more actively in the process of monitoring Special Autonomy as an extension of the indigenous Papuan community, as well as the formation of a DPRP at the Regency level.